The effectiveness of exclusive breastfeeding counseling in expectants in Kutai Kartanegara - Ismi Mufiddah; Ira Paramastri; Trisno Agung Wibowo (Fakultas Kedokteran Universitas Gadjah Mada, 2016)
Effectiveness of counseling to increase exclusive breastfeeding practice among pregnant women in Tenggarong, Kutai KartanegaraPurposeThis research aimed to examine the effectiveness of breastfeeding counseling, to increase knowledge, attitudes, perception for behavioral control, intention and behavior of mothers in exclusive breastfeeding (EBF).MethodsA quasi-experiment study was conducted by comparing an experimental group (29 participants) and a control group (29 participants). The research was conducted in two public health center at different districts at Kutai Kartanegara. Respondents were pregnant women attending antenatal care. The independent variable was breastfeeding counseling, while dependent variables included knowledge, attitudes, perceived behavioral control, intention and behavior of mother on exclusive breastfeeding.ResultsBreastfeeding counseling during pregnancy increased knowledge about EBF. Counselling increased intentions to EBF as well. However, statistical analyses showed that counseling did not make changes to pregnant women’s attitude, perceived behavioral control, and intention to provide EBF. Similarly, there was no difference regarding the behavioral control and attitude towards EBF.ConclusionCounseling increased knowledge and intention to EBF. However, knowledge and intention were not necessarily improved with behavior in terms of EBF. Further research is needed to improve educational techniques.